A comparative view of the educational systems of Greece, France and England. (18th July 2022) - Mavrikakis, Evaggelos; Brinia, Vasiliki; Gkouma, Andriani
This study aims to explore the dividing lines between the educational systems of three countries, Greece, France and England on the areas of public participation, staffing of structures, administration and supervision, assessment, curriculums and funding. Each of these systems has developed a different control system, established roles, frameworks as well as procedures that define to a certain degree its dimension of roles. The study was based on literature review concerning these systems, educational administration, organisational behaviour and management of school units. Basic dimensions of educational policies were studied in order to comprehend each system's approach. The study indicated basic differences between the three systems on decision making, bodies implicated, organisational behaviour and system effectiveness. These differences provide significant insights on systems' characteristics in order to enhance their future development and autonomy, as they are constantly affected by global, political, social, economic and cultural changes. Conclusions are discussed.